The Nature of Civilization, Its Constituents, Its Deterioration, the Islamic Perspective on It - Al-Naemi, Amer Ali (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to shed light on civilization in terms of its essence, the time cycle, the relationship between it, culture and civilization, the role of the state or the political system in preserving civilization, and deducing the state of civilization in the contexts of the verses of the Holy Qur’an to measure the Islamic perspective on it. Methods: The study is based on the inductive historical method, which involves tracing back to the origins of the terms used in the study, examining and measuring the dimensions of the changes that have occurred to them. It also utilizes the descriptive method by presenting and describing the theories that have addressed civilization, and the analytical method by applying theories to historical facts and events, examining their consequences through analysis and deduction. Additionally, the comparative method is employed by comparing theories that discuss civilization to extract the commonalities and divergences. Lastly, the deductive method is used to infer the state of civilization from the texts of the Holy Qur’an. Results: The study concluded that civilization is characterized by presence and appearance, refinement and progress, and is preceded by a state of nomadism. The distinguishing factor of civilization is stability. Civilizations often emerge in the form of states or political systems, while culture is a characteristic found in all peoples of the world. In contrast, civilization is considered an indicator of an advanced stage that combines culture and urbanization. According to its proponents, civilization goes through three general phases: a dominant spirit during its inception, the dominance of reason and materialism at its peak, and its decline and disintegration during a phase of moral decay, excessive indulgence, and the breakdown of the ethical system. The Islamic perspective on civilization is linked to human effectiveness. When humans rise, civilization thrives, and when they decline, it reverts to primitiveness. Conclusions: This study concludes that civilization is the result of diligent human work. This study emphasizes the exploration of the factors of nationalism and religion and their impact on Arab societies and the course of civilization.